2015
DOI: 10.14814/phy2.12561
|View full text |Cite
|
Sign up to set email alerts
|

Contributions of cardiac “funny” (f) channels and sarcoplasmic reticulum Ca2+in regulating beating rate of mouse and guinea pig sinoatrial node

Abstract: The aim of this study was to investigate the effects on spontaneous beating rate of mouse atrial preparations following selective block of cardiac “funny” (f) channels, I(f), and/or suppression of sarcoplasmic reticulum (SR) function in the absence and presence of β‐adrenoceptor stimulation. ZD7288 [to block I(f)] caused a substantial reduction (222 ± 13 bpm) in beating rate from 431 ± 14 to 209 ± 14 bpm, ryanodine alone (to block SR Ca2+ release) reduced beating rate by 105 ± 11 bpm, with subsequent addition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 31 publications
(83 reference statements)
0
9
0
Order By: Relevance
“…[3][4][5] Although the physiologic mechanisms by which utPMCs function are poorly studied, Ca 2+ signaling and an internal Ca 2+ clock are thought to regulate their activity in a manner similar to that of heart and gut PMCs. [7][8][9][10][11][12][13][14][15][16][17] Disruption of coordinated ureteric contraction causes nonobstructive hydronephrosis, defined as dilatation of the renal pelvis and ureter without physical obstruction to urinary flow. Previously, we demonstrated that decreased Hedgehog signaling during mouse kidney development results in nonobstructive hydronephrosis.…”
Section: Significance Statementmentioning
confidence: 99%
See 1 more Smart Citation
“…[3][4][5] Although the physiologic mechanisms by which utPMCs function are poorly studied, Ca 2+ signaling and an internal Ca 2+ clock are thought to regulate their activity in a manner similar to that of heart and gut PMCs. [7][8][9][10][11][12][13][14][15][16][17] Disruption of coordinated ureteric contraction causes nonobstructive hydronephrosis, defined as dilatation of the renal pelvis and ureter without physical obstruction to urinary flow. Previously, we demonstrated that decreased Hedgehog signaling during mouse kidney development results in nonobstructive hydronephrosis.…”
Section: Significance Statementmentioning
confidence: 99%
“…48 Ca 2+ signaling has been described as a major signaling pathway in PMC in the heart, gut, and the urinary tract. 8,11,12,[14][15][16][17] PTK2b has also been shown to interact with SRC kinase, a known regulator of HCN channels. [49][50][51] Our results indicate that pharmacologic inhibition of PTK2b in pyeloureteric explant tissue significantly reduces ureteric contraction frequency, suggesting that PTK2b controls PMC function.…”
Section: Molecular Markers Of Utpmcsmentioning
confidence: 99%
“…Recent theoretical and experimental studies (10,20,25) have shown that a selective perturbation of only one clock (either M-clock or Ca-clock), namely by ivabradine, a direct I f inhibitor, or by cyclopiazonic acid, a direct SERCA (SR Ca pump) inhibitor, affects the other clock indirectly. If the timing of the ignition phase onset is a universal timing mechanism of the coupled-clock system, an increase in steady-state APCL in response to either ivabradine or cyclopiazonic acid should be similarly linked to a change in the onset of the ignition phase.…”
Section: Time-to-ignition-phase Is a Universal Timing Mechanism For Apcl Regulation By The Coupledclock Systemmentioning
confidence: 99%
“…This is plausible, considering the role of Ca 2+ released from the SR in regulating If in SA node preparations. 21 In bladder overactivity, developed in a rat model following partial bladder outlet obstruction, it was shown that the physiological functioning of ICCs changes and the expression of the HCN channels in bladder ICCs significantly increases. [22][23][24] These findings suggest that the HCN channels and ICCs might play an important role in the pathogenesis of detrusor overactivity.…”
Section: Discussionmentioning
confidence: 99%